2005
DOI: 10.1159/000085356
|View full text |Cite
|
Sign up to set email alerts
|

Results and Complications after Ileal Pouch Anal Anastomosis: A Meta-Analysis of 43 Observational Studies Comprising 9,317 Patients

Abstract: Objective: To analyze the literature of ileal pouch anal anastomosis (IPAA) regarding complications and functional outcome, to provide audit data for individual surgeons and units to assess their own performance against and also to serve as reference standard for the assessment of novel alternatives. Background: IPAA is the standard restorative procedure for ulcerative colitis (UC) and familial adenomatous polyposis (FAP). This operation is, however, associated with distinct rates of failure, complications and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
159
4
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(186 citation statements)
references
References 81 publications
13
159
4
6
Order By: Relevance
“…Fecundity among women with UC before surgery is comparable to a control population of women without UC, but is only 20 % of fecundity rates of controls aft er IPAA ( 326 ). Approximately 20 % of women will have dyspareunia or fecal incontinence during intercourse during a 3-year follow-up aft er IPAA ( 320 ). A meta-analysis of 43 observational studies found a 4 % risk of sexual dysfunction in men postoperatively ( 320 ).…”
Section: Recommendations For Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…Fecundity among women with UC before surgery is comparable to a control population of women without UC, but is only 20 % of fecundity rates of controls aft er IPAA ( 326 ). Approximately 20 % of women will have dyspareunia or fecal incontinence during intercourse during a 3-year follow-up aft er IPAA ( 320 ). A meta-analysis of 43 observational studies found a 4 % risk of sexual dysfunction in men postoperatively ( 320 ).…”
Section: Recommendations For Surgerymentioning
confidence: 99%
“…Nevertheless, there is increasing recognition of the potential complications following IPAA ( 319 ). Besides pouchitis (see below), which may occur in up to 50 % of patients during long-term follow-up, a variety of surgical complications may ensue ( 320 ). A meta-analysis of 17 series of nearly 1,500 patients undergoing IPAA found that when this surgery was performed without a diverting ileostomy, functional outcomes were similar to those of surgery with proximal diversion but there was an increased risk of anastomotic leak.…”
Section: The Patient With Severe Colitis Refractory To Maximal Oral Tmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a poor functional result or pouch-related complications may force permanent faecal diversion with or without pouch excision and therefore, by definition, failure of the pouch. This occurs in approximately 20% of cases depending on the length of follow-up [7]. The most important risk factors for pouch failure are pelvic sepsis [8][9][10][11], Crohn's disease (CD), chronic antibiotic-resistant pouchitis, and 'idiopathic' pouch dysfunction [9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…1 There are several reasons for failure: septic complications, anastomotic complications, irritable pouch syndrome (IPS) and pouchitis, being the most frequent. 4,5 Data on health-related quality of life (HQoL) also show satisfactory results for a majority of pouch-operated patients. 6,7 However, reported results regarding sexual function, i.e.…”
Section: Introductionmentioning
confidence: 99%